Schizophrenia, Spirituality, and Religion - Subagyo, Roni; Pratiwi, Dewi; Ramadhani, Devi Eka; Hasan, Hasan; Diahlaksmi, Sista; Urrachman, Salsabillah Kemangi (Universitas Muhammadiyah Semarang, 2024)
Background: The impact of religion and spirituality on schizophrenia patients' lives is significant yet understudied. Religion can provide hope and purpose but also lead to spiritual distress and delusions. It influences psychopathology, social integration, and treatment outcomes, serving as an effective tool in managing the illness.Objective: This review assesses the link between schizophrenia, spirituality, and religion.Methods: The study utilized electronic searches on schizo-phrenics, mental health, religion, religiosity, religious practices, and spirituality using PubMed and Google Scholar. Relevant articles were identified, including those assessing religion and caregivers of schizophrenia patients. Additionally, textbooks related to schizo-phrenia, religion, and spirituality were included.Results: Religion, faith, and spirituality intertwine as integral aspects of human experience, influencing beliefs, behaviors, and mental health. Recognizing their significance, clinicians must navigate their role in patient care while respecting diverse beliefs. The interaction between religiosity and schizophrenia presents complexities, impacting treatment adherence and outcomes, necessitating a holistic approach to psychiatric care.Conclusion: Religion significantly impacts individuals, including those with psychosis, offering both support and complexities in mental health. Clinicians must acknowledge and address religious aspects sensitively, as they can influence coping mechanisms but also pose risks such as non-adherence to treatment and potential for harm. Integrating religious considerations into clinical practice is crucial for providing holistic mental health care.